Investigating the impact of preslaughter handling intensity on goats: a study on behavior, physiology, blood enzymes, and hormonal responses - Al-Owaimer, Abdullah N.; Suliman, Gamaleldin M.; Alobre, Mohsen M.; Swelum, Ayman A.; Al-Badwi, Mohammed A.; Ba-Awadh, Hani; Sazili, Awis Qurni; Kumar, Pavan; Kaka, Ubedullah (Frontiers Media SA, 2024)
Introduction: The present study evaluated the effect of preslaughter stress intensities on the behavioral, physiological, blood biochemicals, and hormonal responses in goats. Methods: Twenty-seven intact male goats (Ardi breed, 10 months of age, 27 kg liveweight) were divided into three treatment groups viz., the control (C) group, ear pulling (EP) group, and leg pulling (LP) group. Various behavioral, physiological, blood biochemical and hormonal responses were recorded before and after handling. Results and Discussion: The EP and LP goats had a higher frequency and intensity of vocalization as compared to control goats. The preslaughter handling stress intensities had a significant effect on the before and after handling values of heart rate, respiration rate, rectal temperature, and ear temperature. Further, among groups, the glucose value increased significantly upon preslaughter handling as compared to the baseline value. The LP goats had significantly higher after-handling value for lactate dehydrogenase (LDH) as compared to the before-handling value. The catecholamines (adrenaline and noradrenaline) and β-endorphin concentrations increased significantly upon preslaughter handling. The higher physiological, behavioral, blood biochemical, and hormonal response indicated higher preslaughter stress in EP and LP goats. Both levels of intensity revealed unfavorable responses in goats that may adversely affect animal welfare and meat quality. Thus, to ensure minimal adverse effects on behavior, physiology, blood enzymes, and hormonal responses, it is recommended to follow animal welfare principles when implementing preslaughter handling practices.